Implications of Learning Principles in Learning Islamic Religious Education - Muhamad Mugni Sahid; Muhibbin Syah; Bambang Samsul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to discuss learning principles and their implications for Islamic religious education learning. The research method used is a qualitative method with the type of research being library research. There are several principles in learning, including attention and motivation, active participation, direct involvement, repetition, providing challenges, and individual differences. The implication of these learning principles in Islamic religious education learning is that there must be attention to these principles from educators and students so that Islamic religious education learning can run well.